Lithofacies Characterization of the Early – Middle Miocene Succession, Case-Study, South Iraq - Saleh, Afrah Hassan; Awadeesian, Awadees M. R. (Journal of Petroleum Research and Studies, 2019)
The Early – Middle Miocene Ghar and Lower Fars sedimentary succession at the representative oil-well Nu-18 of the Nahr Umr oil field south Iraq; is taken by this study to investigate the sedimentological to reservoir rock facies buildups and related reservoir zonation; as first rock-typing attempt for the both formations. The sedimentological characterization of the Early Miocene Ghar formation is mainly comprised by successive buildups of sands-gravels and sandstones, whereas; the Middle Miocene Lower Fars formation is started by limestone, limestone-marly/marl anhydritic, upgraded into interbedded-series of marl and anhydrite facies, with less-common occurrences of thin-sandstone interlayers, terminated by marl-sandy-section at the upper part of the Formation. A successive depositional succession has established of 2 litho-units for Ghar Formation & 4 members for Lower Fars Formation, with related sedimentary intervals. The composite micro-to-mega pores/multi-fractures system of the carbonate – anhydrite lithofacies buildups, of the Lower Fars Formation reflects a good pore – reservoir characterization framework. Accordingly; the Lower Fars Formation members and the Ghar Formation litho-units has passed into reservoir-layering-scheme, and a reservoir layering system has submitted of: 7 and 2 reservoir-units for Lower Fars and Ghar formations respectively, and symbolized as: LF-B1, LF-B21, LF-B22, LF-B23, LF-C1, LF-D1, LF-D2, and GH-A, GH-B.